Stakeholder Perspectives on Undergraduate Medical Education: Using a Systems Thinking Approach to Explore Interests in Curriculum Composition - Alexander P Royston (Journal of Medical Education and Curricular Development)
Objectives Several stakeholders are formally recognised when designing undergraduate medical curricula, but past studies have failed to identify them with sufficient breadth, to explore their understanding of the system, or examine their views on curriculum composition. This qualitative study drew on elements of systems thinking to better understand the stakeholders in undergraduate medical education and their role and priorities in curriculum composition. Methods This study employed an exploratory qualitative methodology. Participants were initially identified from the General Medical Council's list of stakeholders and were recruited using a combination of convenience, judgmental and snowball sampling. Data were collected through semistructured interviewing. Interviews were descriptively coded and then thematically analysed. Results In total, 18 participants were interviewed about their perspectives on stakeholders, the purpose of the education, along with their ideal weightings for curriculum subjects. The findings suggested that the breadth of stakeholders exceeded the modest list provided by the General Medical Council. The purposes of the education were themed into: (1) safe patient care, (2) social benefit, (3) service provision, (4) student benefit and (5) provider benefit. Safe patient care emerged as a universally shared purpose, although views on the customer varied between participants. Curricula priorities were more diverse, with competing interests favouring different subjects for emphasis in the curriculum, with views on the value of scientific-learning particularly divided. Conclusion Undergraduate medical education likely concerns a broader range of stakeholders than are often engaged. Several stakeholders are formally recognised when designing undergraduate medical curricula but past studies have failed to identify them with sufficient breadth, to explore their understanding of the system, or to examine their views on curriculum composition. This research raised questions about engagement of vital stakeholders and how power is distributed in the system, along with the need to develop roles into the future when renewing curricula.